Exploration of advanced porous organic polymers as a platform for biomimetic catalysis and molecular recognition. Issue 73 (17th August 2020) - Zhang, Pengcheng; Wang, Sai; Ma, Shengqian; Xiao, Feng-Shou; Sun, Qi
Abstract : This Feature article summarizes our progress in the design of biomimetic POPs for catalysis and molecular recognition with enhanced performance. Abstract : Nature has long been a dominant source of inspiration in the area of chemistry, serving as prototypes for the design of materials with proficient performance. In this Feature article, we present our efforts to explore porous organic polymers (POPs) as a platform for the construction of biomimetic materials to enable new technologies to achieve efficient conversions and molecular recognition. For each aspect, we first present the chemical basis of nature, followed by depicting the principles and design strategies involved for functionalizing POPs along with a summary of critical requirements for materials, culminating in a demonstration of unique features of POPs. Our endeavours in using POPs to address the fundamental scientific problems related to biomimetic catalysis and adsorption are then illustrated to show their enormous potential and capabilities for applications ranging from concerted catalysis to radionuclide sequestration. To conclude, we present a personal perspective on the challenges and opportunities in this emerging field.